THEORETIKAL ASPECTS OF THE UNIVERSALIZATION OF OCCUPATIONAL RISK ASSESSMENT - Журавська, Наталія; Стефанович, Іван; Стефанович, Павло (SWorldJournal, 2023)
The article considers the use of knowledge on theoretical aspects of the universalization of professional risk assessment. For this purpose, an analysis of the latest research and publications was made, and the qualities and combined methods of assessing